Search for a charged Higgs boson produced in the vector-boson fusion mode with decay H±→W±Z using pp collisions at √s = 8 TeV with the ATLAS experiment - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; et al. (Physical review letters, 2015)
A search for a charged Higgs boson, H±, decaying to a W± boson and a Z boson is presented. The search is based on 20.3  fb−1 of proton-proton collision data at a center-of-mass energy of 8 TeV recorded with the ATLAS detector at the LHC. The H± boson is assumed to be produced via vector-boson fusion and the decays W±→q¯q′ and Z→e+e−/μ+μ− are considered. The search is performed in a range of charged Higgs boson masses from 200 to 1000 GeV. No evidence for the production of an H± boson is observed. Upper limits of 31–1020 fb at 95% C.L. are placed on the cross section for vector-boson fusion production of an H± boson times its branching fraction to W±Z. The limits are compared with predictions from the Georgi-Machacek Higgs triplet model.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, M. Geisler, P. Hanke, J. Jongmanns, E.-E. Kluge, A. Kugel, V. Lang, K. Meier, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, M. Wessels [und 2803 weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Im Titel sind die Zeichen + und - hochgestellt
Gesehen am 14.07.2021